Pengaruh Komisaris Independen, Komite Audit, Kepemilikan Institusional, Leverage dan Ukuran Perusahaan Terhadap Integritas Laporan Keuangan - Triani, Yuli; Friyani, Rita; Olimsar, Fredy (Jurnal Akuntansi & Keuangan Unja, 2025)
This study aims to determine the effect of independent commissioner variables, audit committee, institutional ownership, leverage and company size on the integrity of financial statements (Infrastructure Sector Listed on the Indonesia Stock Exchange for the 2021-2024 Period). The sampling technique used was purposive sampling and obtained 43 companies as samples from a total population of 57 companies. The observation period in this study was 4 years, namely from 2021-2024 so that 172 data were obtained. Data processing using SPSS.29 software. This study proves that independent commissioners and institutional ownership affect the integrity of financial statements, while the audit committee, leverage and company size have no effect on the integrity of financial statements. The results of this study emphasize the importance of strengthening the role of independent commissioners and encouraging institutional investor participation in the capital market. Regulators such as the OJK can create stricter policies regarding the number, qualifications, and independence of commissioners as well as transparency of institutional ownership.